2013
DOI: 10.1111/inr.12018
|View full text |Cite
|
Sign up to set email alerts
|

Leadership styles in ethical dilemmas when head nurses make decisions

Abstract: The results highlight the need for head nurses to reflect on their practices and to find new ways of learning from practice, colleagues and patients. Head nurses' managerial decisions due to their 'executive power' can turn into a new state-of-the-art leadership in nursing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Other studies have examined ethical problems and dilemmas from the perspectives of nurse managers or head nurses. 1,4,11 13…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have examined ethical problems and dilemmas from the perspectives of nurse managers or head nurses. 1,4,11 13…”
Section: Introductionmentioning
confidence: 99%
“…These may have been true considering that, in all probability, attention to Indonesian nursing development is more focused on practice than on leadership. A similar concern was reflected in a study conducted amongst Lithuanian nurses in which the researchers concluded that leadership in nursing is typically assumed to be a less important aspect than skills/practice improvement (Zydziunaite, Lepaite, & Suominen, ).…”
Section: Discussionmentioning
confidence: 85%
“…It is well known that nurse leaders experience difficult ethical dilemmas, which in turn can be experienced as personally burdensome and cause stress. (Birkholz et al , 2022; Cooper et al , 2004; Zydziunaite et al , 2013).…”
Section: Discussionmentioning
confidence: 99%